Ilmenite-type MgTiO3 ceramics by complex (Mn1/2W1/2)4+ cation co-substitution producing improved microwave characteristics. Issue 15 (1st August 2021) - Fang, Zixuan; Yang, Hongyu; Yang, Hongcheng; Xiong, Zhe; Zhang, Xing; Zhao, Peng; Tang, Bin
Abstract: In this article, the (Mn1/2 W1/2 ) 4+ complex cation co-doped ilmenite MgTiO3 ceramics with improved microwave characteristics were synthesized. The correlations between the crystal structural evolution induced by ionic substitution and the microwave characteristics were investigated using the structural analysis and the P–V–L bond theory. Theoretically, the Mg–O bond should have a larger value of covalency than Ti–O bond, attributing to the distribution of densities of states, where the s and p states of the Mg atom overlap with those of the O atom. This conclusion fits well the bond theory estimation. The dielectric constant is dominated predominantly by the average bond covalency, which is intrinsically caused by the increase of doping contents. Moreover, the structural stability declines slightly with the increase of (Mn1/2 W1/2 ) contents. From the perspective of structural evolution, this dielectric performance is also reflected by the variations of the Raman shift and the FWHM value of Ag 5 mode. The actual Q × f value, however, experiences a great enhancement at x  = 0.010, which benefits generally from the uniformity of the grain size and the inhibition of reduction of Ti 4+ valence. The excellent microwave characteristics of MgTi0.99 (Mn1/2 W1/2 )0.01 O3 ceramics were achieved: a ε r of 18.74, a Q × f value of 160992 GHz and a τf of −58.2 ppm/°C, when sintered at 1325 °C.